Resolution of Agrarian Conflict in the Santoso Area of Palembang City (A Case Study of Authorities and Community in the Santoso, Palembang City) - Adhyasa, Wahyu Pratama (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
The title of this study is "Resolving Agrarian Conflict in the Santoso Region, Palembang City (A Case Study of Authorities and Community in Santoso Region, Sukari Village, Palembang City)." The Santoso area is situated near the TNI AU Air Base Sri Mulyono Herlambang, and according to local residents, its establishment dates back to around 1959.This research employs descriptive qualitative methods, with primary data sourced from the Santoso Community in Sukarame Village, Palembang City. Secondary data include literature from books, journals, documentation, and information gathered from the community involved in the research problem. Data collection techniques involve observations, documentation, and interviews. Data analysis comprises qualitative methodologies such as data reduction, data presentation, and drawing conclusions through verification.The findings of this thesis reveal that conflict resolution ensued following consultations among various stakeholders to reach a compromise, resulting in peace between the Santoso Community and the Indonesian National Army. However, it is unfortunate that this peace was not formalized in written agreements but remained verbal. Consequently, residents of Santoso still perceive an absence of complete peace and harbor concerns about potential recurrences of conflict